Analisis Peran Latihan Laut Militer dalam Meningkatkan Profesionalisme Prajurit dan Kesiapan Operasi Kolinlamil - Wahyu Utomo, Agus (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2025)
Military sea training has a crucial role in increasing the professionalism of soldiers and the operational readiness of the Military Seaborne Command (Kolinlamil). However, the effectiveness of these exercises still faces various challenges, including limited resources, lack of realism in training scenarios, as well as obstacles in the use of technology and coordination between units. This research aims to explore how maritime training can be optimized to increase Kolinlamil's competence and readiness in facing dynamic and complex threats. The research method used was qualitative, with data collection through direct observation and in-depth interviews with soldiers, unit commanders and military strategists. The collected data was then analyzed through coding, categorization, and interpretation to identify the main themes that emerged. The research results show that although maritime exercises have contributed to improving soldiers' technical skills, there is still an urgent need to improve the realism of the exercises, increase the use and training of technology, and strengthen coordination between units. Thus, optimizing military sea training is necessary to increase Kolinlamil's operational readiness, so that it is able to respond to various threats more effectively and efficiently.